2014
DOI: 10.1097/01.ogx.0000451483.95359.a8
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bacteria in Adult Women With Urgency Urinary Incontinence

Abstract: Introduction and hypothesis-This study's aims were to detect and quantify bacterial DNA in the urine of randomized trial participants about to undergo treatment for urinary urgency incontinence (UUI) without clinical evidence of urinary tract infection (UTI) and to determine if the presence of bacterial DNA in baseline urine relates to either baseline urinary symptoms or UTI risk after urinary tract instrumentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…From an early study that sought to describe FUM variability in women seeking UUI treatment, we reported an association between symptom severity and FUM diversity, including the number and identity of detected bacteria. We also observed evidence of a protective relationship between UTI and the pre-treatment FUM after urinary tract instrumentation (19,21). In another study, our group compared the baseline FUM of women with and without symptoms of UUI.…”
Section: The Fum and Uisupporting
confidence: 57%
See 2 more Smart Citations
“…From an early study that sought to describe FUM variability in women seeking UUI treatment, we reported an association between symptom severity and FUM diversity, including the number and identity of detected bacteria. We also observed evidence of a protective relationship between UTI and the pre-treatment FUM after urinary tract instrumentation (19,21). In another study, our group compared the baseline FUM of women with and without symptoms of UUI.…”
Section: The Fum and Uisupporting
confidence: 57%
“…In light of the improved detection and description of the FUM, these common-sense recommendations are likely to require additional nuance, as the symptoms and clinically important tests for UTI are refined. If beneficial members of the FUM protect women against UTI, and there is some preliminary evidence that they do (19,21), then improper use of antibiotics may be detrimental, at least for some individuals. The existence of the FUM also challenges UTI researchers to reassess their results in animal models that were designed with the assumption that the animal's bladder was sterile.…”
Section: The Fum and Utimentioning
confidence: 99%
See 1 more Smart Citation
“…Since the discovery and confirmation of live bacteria in the bladders of adult women (urobiome), there has been growing interest in the relationship between the urobiome and lower urinary tract symptoms (LUTS), including urinary incontinence (UI). Prior reports of studies that analysed urine samples obtained from the urinary bladder by transurethral catheterisation suggest a difference in urobiome characteristics between women with urge urinary incontinence (UUI) and a control group of unaffected continent women .…”
Section: Introductionmentioning
confidence: 99%
“…The way in which these organisms exist and interact with their environment is called the microbiome [4]. Several studies have now identified differences in the bacterial load [5] and species present [6] in urine taken from women with overactive bladder (OAB) compared to healthy controls. The presence of low levels of bacteria in the bladder could be considered as an interesting idiosyncrasy without any consequences but importantly these differences are associated with clinical symptoms and outcomes [7][8].…”
Section: Introductionmentioning
confidence: 99%